Peran Kepala Sekolah Sebagai Agen Perubahan Visioner Dalam Pengembangan Pendidikan - yiyik nurdiana (Tamilis Synex: Multidimensional Collaboration, 2024)
The purpose of writing this scientific work is to determine the role of principals as visionary agents of change in current educational development. This research uses literature review research, namely a comprehensive literature review method by taking information from various sources such as scientific journals, textbooks and research reports. Analysis is carried out descriptively by identifying main themes, summarizing various information, and interpreting various findings to draw conclusions. The result of this research are that the role of the principal in providing direction, guidance and change is very important for educational development, through the formation of values and norms in school. The principal’s appropriate leadership strategy for realizing educational development can be seen through the principal’s way of working, implementing the school’s vision, as well as his responsibilities for various matters related to changes in developing education. The data obtained shows that as agents of change, principals have an important role, namely building and growing awareness of change for the better and developing and creating a vision and mission of change for educational development.